Manganese Active Transport in Escherichia coli - Silver, Simon (1970)
Manganese was accumulated by cells of Escherichia coli by means of an active transport system quite independent of the magnesium transport system. When the radioisotope (54)Mn was used, manganese transport showed saturation kinetics with a K(m) of 2 × 10(−7)m and a V(max) of 1 to 4 nmoles/min per 10(12) cells at 25 C. The manganese transport system is highly specific; magnesium and calcium did not stimulate, inhibit, or compete with manganese for cellular uptake. Cobalt and iron specifically interfered with (54)Mn uptake, but only when added at concentrations 100 times higher than the K(m) for manganese. Active transport of manganese is temperature- and energy-dependent: uptake of (54)Mn was inhibited by cyanide, dinitrophenol, and m-chlorophenyl carbonylcyanide hydrazone (CCCP). Furthermore, the turnover or exit of manganese from intact cells was inhibited by energy poisons such as dinitrophenol and CCCP.